1996
DOI: 10.1111/j.1399-6576.1996.tb04532.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of warming intravenous fluids on intraoperative hypothermia and postoperative shivering during prolonged abdominal surgery

Abstract: In conclusion, infusion of warmed fluids, combined with skin-surface warming, helps to prevent hypothermia and reduces the incidence of postoperative shivering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 19 publications
0
49
0
4
Order By: Relevance
“…In fact the infusion of crystalloid solutions at room temperature may significantly contribute to intraoperative hypothermia because warming fluids to core temperature requires body heat. Several studies had demonstrated that infusion of warmed fluids helps in the prevention of hypothermia and reduce the incidence of postoperative shivering [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In fact the infusion of crystalloid solutions at room temperature may significantly contribute to intraoperative hypothermia because warming fluids to core temperature requires body heat. Several studies had demonstrated that infusion of warmed fluids helps in the prevention of hypothermia and reduce the incidence of postoperative shivering [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain normothermia, fluid warmers are designed to deliver fluid around body temperature (37°C), and their use has been recommended for all intra-operative infusions ≥ 500 ml in adults [1]. Administration of warmed intravenous fluids in conjunction with standard heat conservation measures has been shown to reduce the incidence of accidental peri-operative hypothermia significantly in gynaecological [8] and abdominal [9] surgery, as well as associated complications during orthopaedic lists [10]. In obstetric practice, the use of intra-operative warmed fluid is also associated with significantly higher Apgar scores in the newborn infant following caesarean section [11].…”
Section: Intravenous Fluid Warming Devicesmentioning
confidence: 99%
“…It has been reported that the intra-operative core temperature is maintained with an acceptably low incidence of hypothermia (9%) on admission to the postanaesthesia care unit (PACU) in grade-3 obese patients when active forced-air warming had been used during bariatric surgery [11]. Intraoperative warming strategies have minimised, but do not prevent, unintentional peri-operative hypothermia in non-obese patients [12][13][14].…”
mentioning
confidence: 99%